Design and development of hybrid polymeric bioinks for 3D bioprinting in tissue engineering - Torres Ayala, Lizardo Kendy (2025)
The formulation of materials for 3D bioprinting involves more than meeting isolated technical specifications. It demands a coordinated understanding of flow behavior, structural integrity, and biological performance. In extrusion-based biofabrication, this complexity becomes particularly visible: a printable hydrogel must deform under pressure, recover its shape after deposition, and remain stable long enough to support tissue formation. This thesis addresses that challenge through the development of a hybrid hydrogel based on alginate and xanthan gum. These polymers were selected for their complementary roles: alginate offers biocompatibility and ionic crosslinking capacity, while xanthan gum modulates viscosity and enhances mechanical response. The formulation process was guided by a systematic rheological framework, incorporating both rotational and oscillatory tests to characterize shear-thinning behavior, yield stress, and viscoelastic recovery parameters essential for anticipating performance under printing conditions. Beyond printability, the material was functionalized with curcumin, in both free and nanoparticle-loaded forms, to evaluate its potential for localized drug delivery. Swelling behavior, antibacterial activity, and release kinetics were analyzed to assess its suitability as a therapeutic reservoir. Finally, in vitro cytocompatibility was assessed using a human gastric epithelial cell line under ISO 10993-5 and ASTM F2739 guidelines, completing a multiscale evaluation of the system.